Analisis Kualitatif Uji Strip Sildenafi l Sitrat dengan Kombinasi Beberapa Reagen dalam Membran Kertas Selulosa - Yessy Gladiani Sutrisno; Siska Khoirunnisa; Diani Sri Agustien; Eva Karyati; Nabila Fasya; Hendri Wasito (Fakultas Farmasi Universitas Pancasila, 2017)
Sildenafi l citrate was widely used to treat erectile dysfunction in men. The high demand of this drug, infl uence of counterfeit drugs. Therefore, it is required an analytical method to determine the authenticity of this drug. The aims of this research were to develop and evaluate of strip test for sildenafi l sitrat identifi cation. Research was conducted by preparation of solution and choosing the appropriate reagent for sildenafi l citrate. The optimum reagents were immobilized in cellulose paper followed by manufactured into strip test. Product performance was evaluated by evaluating several test in termed of qualitative, reproducibility, specifi city and response time. The results showed that the optimum membrane product was consisted of copper sulfate and sodium bicarbonate (2:1); ammonium ferric sulfate hexahydrate and copper acetat (1:3); sodium sulfate, copper acetate and ammonium ferrite sulfate (2:1:1) and mercury acetate and copper sulfate (2:1) reagents. The strip test had a capability in specifi c identify of sildenafi l citrate with a good reproducibility and less than ten seconds for time response. The strip test developed could be used as an early detection tool for the authenticity of a sildenafi l citrate tablet which more rapid.